Beneficial Impact of Interspecies Chimeric Renal Organoids Against a Xenogeneic Immune Response - Saito, Yatsumu; Matsumoto, Naoto; Yamanaka, Shuichiro; Yokoo, Takashi; Kobayashi, Eiji (Frontiers in Immunology, 2022)
Background Animal fetal kidneys have the potential to be used as scaffolds for organ regeneration. We generated interspecies chimeric renal organoids by adding heterologous rat renal progenitor cells to single cells from mouse fetal kidneys and applying the renal development mechanism of mouse fetuses to rat renal progenitor cells to examine whether rat renal progenitor cells can differentiate into renal tissues of the three progenitor cell lineages of kidneys between different species. Furthermore, we investigated whether chimeric renal organoids with an increased proportion of recipient cells reduce xenogeneic rejection. Methods C57BL/6JJmsSlc mice (B6 mice) and Sprague-Dawley-Tg (CAG-EGFP) rat (GFP rats) fetuses were used as donors, and mature male NOD/Shi-scid, IL-2RγKO Jic mice (NOG mice) and Sprague-Dawley rats (SD rats) were used as recipients. First, fetal kidneys were removed from E13.5 B6 mice or E15.5 GFP rats and enzymatically dissociated into single cells. These cells were then mixed in equal proportions to produce chimeric renal organoids in vitro. The chimeric organoids were transplanted under the renal capsule of NOG mice, and maturation of the renal tissues in the organoids was observed histologically. Furthermore, chimeric organoids were prepared by changing the ratio of cells derived from mouse and rat fetal kidneys and transplanted under the renal capsule of SD rats subjected to mild immunosuppression to pathologically analyze the strength of the xenogeneic immune response. Results The cap mesenchyme was reconstructed in vitro, and nephron progenitor cells and ureteric buds were mosaically comprised GFP-negative mouse and GFP-positive rat cells. In the in vivo environment of immunodeficient mice, chimeric renal organoids mosaically differentiated and matured into renal tissues of three lineages. Chimeric renal organoids with high rates of recipient rat cells showed milder rejection than complete xenograft organoids. The vessels of recipient rats entered from the periphery of the transplanted chimeric renal organoids, which might reduce their immunogenicity. Conclusion Interspecies chimeric renal organoids may differentiate into mature renal tissues of each renal progenitor cell lineage. Furthermore, they may reduce transplant rejection compared with xenograft organoids.